The impact of SCAMPER and Baron's Techniques on the Development of English Language Critical Thinking Skills: Applied Study on 10th Grade Students - Abdallah Azzam Al - Jarrah; Maram Abdel Fattah Al Tarawneh (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims at identifying the impact of SCAMPER and Baron`s models on the development of English Language critical thinking. The sample consisted of (112) 10th graders students at Asma Bent Abi Baker secondary school (ABAB) in the first educational directorate of Amman, the capital. The current study used the semi-experimental method to apply both models to two experimental groups and one control group. The study instruments were developed according to SCAMPER, the teaching thinking model, to be applied to the first experimental group of (36) students; and Baron, the good thinker model, to be applied to the second experimental group of (38) students; whilst the control group of (38) students taught by the conventional teaching method. All experiments were separately conducted using the designed critical thinking skills, test, which evaluates the English language skills (interpretation, inference, and deduction) against the SCAMPER and Baron`s techniques based on the content of the first two units in the first term of the 10th grader's English curriculum. The results showed that there are slight statistically significant differences between the experimental groups, SCAMPER's group and Baron`s, in favor of SCAMPER; however, there was a considerable significant difference when compared with the control group. This ensures the effectiveness of applying both models in developing critical thinking skills among 10th students with the superiority of the SCAMPER model. Finally, the current study recommends conducting future studies to investigate the impact of SCAMPER and Baron techniques.